The effect of scaffolding-based digital instructional media on higher-order thinking skills - Setyaningrum, Wahyu; Pastoriko, Fransiskus Magnis; Fabian, Khristin; Ying, Chiang Yi (Journal on Mathematics Education, 2024)
Higher-order thinking skills (HOTS) are widely recognized as an essential for addressing the challenges of modern life. As a result, numerous educational systems prioritize the development of students' HOTS. While previous studies have explored the impact of scaffolding on HOTS through either paper-based methods or gamified approaches, this experimental study seeks to examine the effects of scaffolding-based digital instructional media delivered via web-based instruction—specifically, the platform Madmatics—on students' HOTS. The participants in this study consisted of 64 junior high school students, with 32 students utilizing the scaffolding-based digital media for mathematics learning, while the remaining 32 students engaged in traditional paper-and-pencil exercises in a regular classroom setting. The findings reveal that students exposed to scaffolding-based digital instructional media demonstrated significantly greater improvements in HOTS compared to those in the conventional learning environment. Three key factors may explain this enhancement: the scaffolding guided students through problem-solving tasks, the media provided immediate feedback and explanations to facilitate learning, and the digital platform increased student engagement and motivation to solve mathematical problems.